2010
DOI: 10.3989/gya.112309
|View full text |Cite
|
Sign up to set email alerts
|

Emulsiones alimentarias aceite-en-agua estabilizadas con proteínas de atún

Abstract: This work is focused on the development of o/w salad dressing-type emulsions stabilized by tuna proteins. The influence of protein conservation methods after the extraction process (freezing or liofilization) on the rheological properties and microstructure of these emulsions was analyzed. Processing variables during emulsification were also evaluated. Stable emulsions with adequate rheological and microstructural characteristics were prepared using 70% oil and 0.50% tuna proteins. From the experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The membrane interfacial resistance against coalescence depends largely on the concentration of the emulsifier molecules, their chemical properties and structural dimensions, the electrical charge of the emulsifier and the intermolecular interactions (SAIKI et al, 2007;THANASUKARN et al, 2004). In addition, Ruiz-Márquez et al (2010), prepared oil-in-water emulsions made with tuna proteins and found that the dynamic viscoelastic functions showed behaviour similar to that of the emulsion of the present study.…”
Section: Determination Of a Linear Viscoelastic Zonesupporting
confidence: 55%
See 1 more Smart Citation
“…The membrane interfacial resistance against coalescence depends largely on the concentration of the emulsifier molecules, their chemical properties and structural dimensions, the electrical charge of the emulsifier and the intermolecular interactions (SAIKI et al, 2007;THANASUKARN et al, 2004). In addition, Ruiz-Márquez et al (2010), prepared oil-in-water emulsions made with tuna proteins and found that the dynamic viscoelastic functions showed behaviour similar to that of the emulsion of the present study.…”
Section: Determination Of a Linear Viscoelastic Zonesupporting
confidence: 55%
“…In the stability studies, after eight months Lorenzo et al (2008) were able to visually observe low fat emulsion destabilization in a blend of guar gum and xanthan gum (2% maximum), Some studies have demonstrated a dependence on the storage modulus and loss modulus related to the frequency, as well as a close relationship with the nature of the emulsifier used, and the method used to manufacture the emulsion (RUIZ-MÁRQUEZ et al, 2010). As in the case of Taherian et al (2011), the addition of whey protein resulted in a decrease in G' and G'' as the storage time progressed, which is indicative of a destabilizing type of emulsion, consistent with the results of the present study.…”
Section: Frequency Sweepsmentioning
confidence: 99%
“…Surfactants obtained directly from renewable natural materials are gaining more and more attention since they are more eco-friendly than traditional ones (Gómez, 2009;Ruiz-Márquez et al, 2010). Polyoxyethylene glycerol esters derived from cocoa oil are non-ionic surfactants obtained from a renewable source which fulfill the environmental and toxicological requirements to be used as emulsifying agents (Bermejo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While the best known of proteins for use as emulsifiers raw materials are animal origin i.e., eggs and milk, vegetable sources are being used increasingly, such as soybean, peas, lupins or wheat gluten (Bengoechea, et al, 2006(Bengoechea, et al, , 2008Ruiz-Márquez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%